The books of Enoch or 1 Enoch : the complete and original edition, also includes the book of Jasher and the book of Jubilees - Charles, R. H. (Robert Henry), 1855-1931 (Oxford.: : Clarendon press, 1912)
"A collection of three key "lost" books of the bible, offering insight into the origins of early Christianity. In the early days of the Christian faith there were many writings, only some of which became part of the canonical Bible. But what of the other books, known as apocryphal texts...which of those are worth reading? One of the most influential and well-known of these apocryphal texts is The Books of Enoch, a collection of three ancient Hebrew texts that contain teachings about angels, demons, the great flood, as well as mystical prophecies. This collection also includes two other important apocryphal books. The Book of Jasher, meaning "upright" or "righteous" describes the world's creation up until Moses' death and is referenced throughout the Hebrew bible. The Book of Jubilees is an ancient Jewish religious text that offers a retelling of the books of Genesis and Exodus. Compiled together for modern readers, these three apocryphal texts offer insight into the origins of early Christianity. Readers will discover new details, narratives, and perspectives that will interest, and even challenge, modern readers. Together, these books provide a historical framework for readers interested in expanding their knowledge of biblical heritage"--
Keywords: Ethiopic book of Enoch -- Criticism, interpretation, etc; Sefer ha-yashar (Quasi-historical work) -- Criticism, interpretation, etc; Book of Jubilees -- Criticism, interpretation, etc; Apocryphal books -- Criticism, interpretation, etc